2018
DOI: 10.4172/2155-9546.1000537
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Puberty in Red Spotted Grouper, Epinephelus akaara By Water Temperature

Abstract: It takes quite a long time for the grouper to spawn. In the case of red spotted grouper (Epinephelus akaara), at least three to four years of rearing is usually required to reproduce them for the first time. Reproductive control techniques can be applied to repress, delay or advance the onset of puberty. Thus, they can be used to accelerate the process of selective breeding in this species. The present study investigated whether alterations of rearing water temperature (WT) can advance the onset of puberty in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…However, in the second month, from 24 August to 23 September, the average water temperature was only 23.4 °C. In previous studies, it was shown that higher water temperatures could induce faster growth of channel catfish, Ictalurus punctatus [ 39 ], largemouth bass, Micropterus salmoides [ 40 ], and red spotted grouper [ 41 ]. In this study, it was possibly the higher water temperature and white LED that caused the red spotted grouper to achieve a significantly higher CF in the first month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the second month, from 24 August to 23 September, the average water temperature was only 23.4 °C. In previous studies, it was shown that higher water temperatures could induce faster growth of channel catfish, Ictalurus punctatus [ 39 ], largemouth bass, Micropterus salmoides [ 40 ], and red spotted grouper [ 41 ]. In this study, it was possibly the higher water temperature and white LED that caused the red spotted grouper to achieve a significantly higher CF in the first month.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences in FSHβ and LHβ expression among the four light groups. Recently, the endocrine system of the Kiss-GnRH-GtHs axis was considered a potent regulator of reproduction in grass puffer [ 48 ], European sea bass [ 49 , 50 ], striped bass, Morone saxatilis [ 51 ], and red spotted grouper [ 41 ]. Until now, FSHβ has been widely known to be active as a key hormone in mediating early vitellogenesis and spermatogenesis, whereas LHβ is generally associated with final maturation and ovulation or spermiation in the salmonid fish [ 52 , 53 , 54 ], Japanese conger, Conger myriaster [ 55 ], Japanese eel, Anguilla japonica [ 56 ], and European sea bass [ 57 ].…”
Section: Discussionmentioning
confidence: 99%